Characterization of QSPA plasma streams in plasma-surface interaction experiments: simulation of ITER disduption - Makhlaj, V.A. (Вопросы атомной науки и техники, 2012)
Experimental simulations of thermal stage of ITER disruptions with relevant surface heat loads (energy density up to 30 MJ/m² ) were performed with a quasi-steady-state plasma accelerator QSPA Kh-50. It was found, that the melt motion driven by plasma pressure gradient dominates in tungsten macroscopic erosion, resulting in droplet splashing and formation of the craters with rather large edge ridges of displaced material. The contribution of mass loss to surface erosion is negligible in comparison with surface profile development caused by melt motion. Экспериментальное моделирование тепловой фазы срыва тока в ИТЭР с соответствующими тепловыми нагрузками на поверхности (плотность энергии до 30 МДж/м²) было выполнено в квазистационарном плазменном ускорителе КСПУ Х-50. Было установлено, что движение расплава, обусловленное градиентом давления плазмы, доминирует в макроскопической эрозии вольфрама и приводит к разбрызгиванию капель и образованию кратеров с большими горами перемещенного материала на их границах. Вклад массовых потерь в эрозию поверхности пренебрежимо мала по сравнению с развитием профиля поверхности, обусловленным движением расплава. Експериментальне моделювання теплової фази зрива струму в ІТЕР з відповідними тепловими навантаженнями на поверхні (густина енергії до 30 МДж/м²) було виконано в квазістаціонарному плазмовому прискорювачі КСПП Х-50. Було встановлено, що рух розплаву, обумовлений градієнтом тиску плазми, домінує в макроскопічній ерозії вольфраму приводить до розбризкування крапель і утворення кратерів з досить великими граничними горами переміщеного матеріалу. Внесок масових втрат в ерозію поверхні э незначним в порівнянні з розвитком профілю поверхні, що обумовлений рухом розплаву.